Territori, the Italian Web Portal of Cadastres and Historical Cartography (Global Journal of Human-Social Science, 2014)
Territori is the Italian web portal of cadastres and historical during 2011 by the company Hyperborea on assignment of the "DirezioneGenerale per gliArchivi". Territori belongs to the National Archival System (SAN) that aims at offering a unique point of access to Italian archiva Territori represents a single access point to the documentation pr State Archives that joined in the project. Every Italian State Archive that reali cataloguing and digitization project of their maps and cadastral sources can join in Ter ritori, improving the global documentation managed by the portal and following its promotion and valori-zation aims.